Diabetes quality of life among elderly diabetic patients and its association - Shalihin, Mohd Shaiful Ehsan; Mukhali, Hassan Basri; Ahmad Zubaidi, Zati Sabrina; Md Aris, Mohd Aznan; Omar, Ahmad Marzuki; Mohammad Aidid, Edre; Fauzi, Abdullah; Zulkifli, Nurul Afiqah; Abdul Aziz, Azrul Aziz (Fakulti Perubatan dan Sains Kesihatan Universiti Putra Malaysia, 2021)
Elderly diabetic patients are increasing worldwide due to improvement in healthcare services provided by most countries. Diabetes comes with morbidities and complications in which the quality of life of geriatric patients should be measured, and the associated factors should be determined. A cross-sectional study was conducted among 269 elderly diabetic patients from all government health clinics of Kuantan. Their ociodemographic data were recorded, and quality of life was measured using validated Diabetes Quality of Life Instrument. Mann Whitney U test and Kruskal Wallis tests were used to identify the issociation between domains of quality of life and variables. The predictors were identified via logistic regression analysis. The majority of patients were female (61%), had a primary level of education (52%), and financial income falls within B40 groups (97.4%). The majority of the clinics were located in rural (61.3%), without the presence of Family Medicine Specialist (77.7%) and managed mainly by medical officers and diabetic educators only (55.8%). Most patients had uncontrolled diabetes (71.7%), uncontrolled blood pressure readings (63.2%) and lipid levels (74.2%). Clinic location, diabetes control status and geriatric age were statistically significant for predicting patients’ diabetes quality of life. This study proved that geriatric patients had a better quality of life by lowering the HbA1c target despite the misconception of the high likelihood of complications among the elderly. Social support and financial status of patients determined the quality of life in the elderly that should be incorporated as assessment parameters of each geriatric visit. Each clinic had its unique management strategy. Those led by family medicine specialists and other major supporting staff usually present in central city provided the best quality of life for patients. Therefore, more primary care physician and local management strategy should be produced.